Very long-term follow-up after in-tunnel patent foramen ovale closure with FlatStent EF: still an attractive option? - Onorato, Eustaquio M.; Ambrosini, Vittorio; Casilli, Francesco; L. Bartorelli, Antonio (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
We present a case of a 38-year-old woman, aura migraineur, with a past medical history of Hashimoto’s thyroiditis and elevated homocysteine level of 75 µmol/l due to homozygous C677T MTHFR gene mutation on folic acid supplementation. In December 2009 a right-sided hemiparesis on awakening occurred and brain magnetic resonance imaging confirmed left thalamic infarct. Continuous ECG monitoring ruled out atrial fibrillation. A Doppler study of lower limbs revealed no overt thrombosis. Extracranial duplex ultrasound examination was normal and carotid dissection was excluded. Two-dimensional (2D) transthoracic/transesophageal echocardiography (TTE/TEE) color Doppler showed a right-to-left shunt (RLS) via a long tunnel-type patent foramen ovale (PFO), with an overlap between the primum and secundum septum of 13 mm along with a prominent Eustachian valve.